A randomized controlled trial of the safety and efficacy of a topical gentamicin–collagen sponge in diabetic patients with a mild foot ulcer infection. (11th May 2018) - Uçkay, Ilker; Kressmann, Benjamin; Di Tommaso, Sébastien; Portela, Marina; Alwan, Heba; Vuagnat, Hubert; Maître, Sophie; Paoli, Christophe; Lipsky, Benjamin A
Objectives: The initial phase of infection of a foot ulcer in a person with diabetes is often categorized as mild. Clinicians usually treat these infections with antimicrobial therapy, often applied topically. Some experts, however, believe that mild diabetic foot ulcer infections will usually heal with local wound care alone, without antimicrobial therapy or dressings. Methods: To evaluate the potential benefit of treatment with a topical antibiotic, we performed a single-center, investigator-blinded pilot study, randomizing (1:1) adult patients with a mild diabetic foot ulcer infection to treatment with a gentamicin–collagen sponge with local care versus local care alone. Systemic antibiotic agents were prohibited. Results: We enrolled a total of 22 patients, 11 in the gentamicin–collagen sponge arm and 11 in the control arm. Overall, at end of therapy, 20 (91%) patients were categorized as achieving clinical cure of infection, and 2 (9%) as significant improvement. At the final study visit, only 12 (56%) of all patients achieved microbiological eradication of all pathogens. There was no difference in either clinical or microbiological outcomes in those who did or did not receive the gentamicin–collagen sponge, which was very well tolerated. Conclusion: The results of this pilot trial suggest that topical antibiotic therapy with gentamicin–collagen sponge, although very well tolerated, does not appear to improve outcomes in mild diabetic foot ulcer infection.